2020
DOI: 10.3389/fmicb.2020.00554
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Screening for New Fungal Polyester Hydrolyzing Enzymes

Abstract: There is a strong need for novel and more efficient polyester hydrolyzing enzymes in order to enable the development of more environmentally friendly plastics recycling processes allowing the closure of the carbon cycle. In this work, a high throughput system on microplate scale was used to screen a high number of fungi for their ability to produce polyester-hydrolyzing enzymes. For induction of responsible enzymes, the fungi were cultivated in presence of aliphatic and aromatic polyesters [poly(1,4butylene ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…All short-chain p-NP-esters were hydrolyzed into p-nitrophenol, with slightly higher activity on those esters based on C 4 , C 6 , and C 8 acids (6.5, 5.8, and 5.5 U ml −1 , respectively) (Figure 1). Therefore, rumen content demonstrated considerably higher esterase activity in comparison with polyester-induced fungal supernatants, where esterase activity accounted for approximately 0.4 U ml −1 with p-NPB (C 4 ) as a model substrate (Weinberger et al, 2020).…”
Section: Identification Of Polyester-degrading Activitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…All short-chain p-NP-esters were hydrolyzed into p-nitrophenol, with slightly higher activity on those esters based on C 4 , C 6 , and C 8 acids (6.5, 5.8, and 5.5 U ml −1 , respectively) (Figure 1). Therefore, rumen content demonstrated considerably higher esterase activity in comparison with polyester-induced fungal supernatants, where esterase activity accounted for approximately 0.4 U ml −1 with p-NPB (C 4 ) as a model substrate (Weinberger et al, 2020).…”
Section: Identification Of Polyester-degrading Activitiesmentioning
confidence: 95%
“…Regarding fungi, different hydrolases (lipase and esterase) from Aspergillus, Penicillium, and Candida species are already exploited at industrial level and found applications in different sectors like detergents, textile industry, diary, and food preparation (Weinberger et al, 2020). Hydrolysis of polyesters and other synthetic polymers was previously described for Penicillium and Beauveria species (Heumann et al, 2006;Liebminger et al, 2007;Almansa et al, 2009).…”
Section: Potential Polyester-degrading Microorganismsmentioning
confidence: 99%
“…Traditional agar plate assays have limited capability in screening large-sized metagenomic libraries. Recent studies in developing high-throughput screening approaches might accelerate the discovery of new plastic-degrading microbes and enzymes [19,20]. When using a functional screening approach, it is important to select a proper host cell for constructing a heterologous gene expression library, with desirable expression level and library representativeness.…”
Section: Glossarymentioning
confidence: 99%
“…Figure 1C shows the commonly used workflow of the proteomic approach for mining plastic-degrading enzymes. First, the pure or environmental microbial consortia are grown with and without the plastic substrate, as the presence of plastics could differentially induce the functional microorganisms to express enzymes with plastic hydrolytic activity [19]. Proteins produced by the microbial cultures are extracted and digested into small peptides, which are subjected to sequencing, followed by protein identification via bioinformatic analysis.…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Polyester hydrolases from fungi and bacteria exhibit excellent hydrolytic activity in converting PET into two environmentally friendly monomers, terephthalic acid and ethylene glycol. [95][96][97][98] The polyester hydrolase from Thermobifida fusca DSM43793 was first reported to degrade PET at 55°C, albeit slowly. In subsequent years, various thermophilic PET hydrolases from thermophilic host microorganisms, both eukaryotic and prokaryotic, have been identified and characterized for PET degradation, with thermal stability at � 70°C.…”
Section: Biotechnology For Plastic Waste Recyclingmentioning
confidence: 99%